Which equation can be solved using the inverse property?log2x = log26
e3.5 = e2x
102x = 10-6
log4x = -1

Answers

Answer 1
Answer: The inverse property of a logarithm is
loga a^x = x
or
a^loga x = x
Therefore,from the choices, the equation than can be solved using the inverse property is
log2x = log26
which if simplified and solved results to
x = 6
Answer 2
Answer:

Answer:

The equation which can be solved by inverse property is: log_(2)x=log_(2) 6.

Step-by-step explanation:

The inverse property of Logarithms:

log_(b)b^(x)=x

or

g(x)=b^(x) \ \text{and} \ \ f(x)=log_(b) x

From the provided option log_(2)x=log_(2) 6 can be solved using the inverse property.

Consider the option 1. log_(2)x=log_(2) 6

Use the inverse property of logarithms:

2^(x)=2^(6)

x=6

Thus, log_(2)x=log_(2) 6 can be solved by inverse property.


Related Questions

Find the slope (3,2), (-4,3)
Horce read 160 pages in 4 hours. how many pages can he read in 6hours
Using the function in example one, what is the y value (output) when x=4?
the gathering of information about public opinion by questioning a representative sample of the population is
Jerry walked a dog from 6:40am to 7:30am one day, Paid at the rate of $6 per hr, how much did he earn that day?

Solve for x. Express the answer in simplest form.
2/1= 8x-2/9

Answers

First, you put known numbers apart ( numbers without x ) and unknown numbers apart (numbers with x ), and of course don't forget that when you move a number from a part to another, his sign change, So you get: 
(2)/(1)  = 8x -  (2)/(9)
(2)/(1) +  (2)/(9) = 8x

Now, you need to have the same denominator so you can add 2/1 and 2/9. So, you multiply 2/1 by 9, so you get:
(2*9)/(1*9) +  (2)/(9) = 8x
(18)/(9) +  (2)/(9) = 8x

Then you add the 2 fractions and you get:
(20)/(9)  = 8x

Now, you divide each term by 8, so you get:
( (20)/(9) )/(8) = (8x)/(8)

in (8x)/(8), you removed 8 and 8 and you get x, so you get:
( (20)/(9) )/(8) = x

as you know, 8 = 8/1, and when you got a division of 2 fractions, you multiply the first by the inverse of the second, which means you get:
(20)/(9) *  (1)/(8) = x

And now you multiply, so you get:
(20*1)/(9*8)
(20)/(72)

20 and 72 have a common factor, so you divide each by 4, and you get:
(20/4)/(72/4)
(5)/(18)

So, x =  (5)/(18)

Hope this Helps! :D




2/1= 8x-2/9
2= 8x-2/9
18=72x-2
20=72x
x=20/72
x= 5/18

Which of the following represents "The product of the abscissa and ordinate is ten"?a)xy = 10
b)10x = y
c)10y = x

Answers

Hello,
if x represents the abscissa
and y the ordinate then
the product is x*y
Answer A

Simplify.
A12 over a7

Answers

Answer:

a^5.

Step-by-step explanation:

a^12 / a^7 = a^(12 - 7) = a^5.

Hope this helps!

The sum of complementary angles is 90 degrees.
a. True
b. False

Answers

TRUE! because they are 90 degrees

Answer:

a. true

Step-by-step explanation:

each month for 6 months, Kelsey completes 5 paintings. How many more paintings does she need to complete before she has completed 38 paintings?

Answers

In one month she completed 5 paintings, so in 6 month she completed 6 * 5 = 30 paintings.

38 - 30 = 8 - that's how many paintings she's still about to complete.

If she can do 5 paintings in one month, she'll do 8 paintings in 1 3/5 months. If we assume that month has 30 days, she'll probalby need one month and 18 days to do it (because 3/5 from 30 is 18).

Final answer:

Kelsey has painted 30 paintings over 6 months. She needs to paint 8 more to reach her goal of 38 paintings.

Explanation:

The subject of this question is mathematics and it sounds like a grade-appropriate question for middle school. To figure out how many more paintings Kelsey needs to complete to reach 38, we can use multiplication and subtraction.

 

First, we multiply the number of paintings Kelsey completes each month (5) by the number of months (6). This gives us a total of 30 paintings.

Then, we subtract this number from the total number of paintings Kelsey wants to complete (38). The result is the number of additional paintings Kelsey needs to complete.    

So, 38 - 30 = 8. Kelsey needs to complete 8 more paintings to reach her goal of 38 paintings.

Learn more about Problem Solving here:

brainly.com/question/31606357

#SPJ3

Square root of-100x^4y^13

Answers

Answer:

10x^2y^6√y

Step-by-step explanation:

1. First, let's factor out any perfect squares from the expression under the square root. In this case, we can factor out 100, which is a perfect square:

√(100 * x^4 * y^13)

2. Taking the square root of 100 gives us 10:

10 * √(x^4 * y^13)

3. Now, let's simplify the expression under the square root. Remember that the square root of a product is equal to the product of the square roots:

10 * √(x^4) * √(y^13)

4. The square root of x^4 is x^2:

10 * x^2 * √(y^13)

5. Finally, let's simplify the square root of y^13. Since 13 is an odd number, we can write it as the product of a perfect square and an additional factor:

10 * x^2 * √(y^12 * y)

6. The square root of y^12 is y^6:

10 * x^2 * y^6 * √y

Therefore, the simplified expression for the square root of -100x^4y^13 is:

10x^2y^6√y